PENERAPAN METODE LINEAR PROGRAMING UNTUK MEMAKSIMALKAN KEUNTUNGAN PENJUALAN BERBASIS QM FOR WINDOWS ( Studi Kasus : Warung Lalapan Sri Ayu) - Muh. Arya Rafandi; David Oni Apaseray, Zulfahmi AS, Muhammad Akbar Maulana; Heru Sutejo (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
Small and Medium-sized Enterprises (SMEs), or Usaha Kecil dan Menengah (UKM) in Indonesian, in the culinary sector, especially traditional Indonesian eateries (warung lalapan), often face production optimization challenges amidst resource limitations. This study aims to analyze the optimal production combination of chicken and duck lalapan portions to maximize daily profit at Warung Lalapan Sri Ayu. The Linear Programming method with a graphical approach was used, utilizing the warung's daily operational data. Results indicate that the optimal production is 15 portions of Duck Lalapan and 0 portions of Chicken Lalapan per day, yielding a profit of Rp 150,000 per day. Work time constraint was identified as the primary limiting factor, while the production cost constraint was non-binding. It is concluded that Warung Lalapan Sri Ayu should focus its strategy on Duck Lalapan and strive to increase work time capacity to enhance potential profits, utilizing the remaining budget for strategic development.